Difference in outcomes of pediatric septic shock after fluid resuscitation according to the Ultrasound-guided Fluid Resuscitation (USFR) and American College of Critical Care Medicine (ACCM) protocols: A randomized clinical trial - Saptadi Yuliarto; Kurniawan Taufiq Kadafi; Nelly Pramita Septiani; Irene Ratridewi; Savitri Laksmi Winaputri (Paediatrica Indonesiana, 2023)
Background Sepsis is a major cause of morbidity and mortality in children. The American College of Critical Care Medicine (ACCM) protocol currently in use in the management of septic shock carries a risk of fluid overload. With the use of ultrasonographic monitoring, the Ultrasound-guided Fluid Resuscitation (USFR) protocol may reduce the incidence of fluid overload and mortality. Objective To assess the difference in outcomes of fluid resuscitation in pediatric septic shock using the USFR vs. ACCM protocols. Methods This randomized clinical trial involved 36 subjects randomized equally into the USFR and ACCM groups. After randomization, each subject was given fluid resuscitation starting at 20 mL/kg and repeated every 5-10 minutes as needed, according to the ACCM protocol. After fluid resuscitation was given, patients in the ACCM group were evaluated for clinical signs, liver span, and rhonchi, whereas those in the USFR group underwent USCOM examination for cardiac index (CI), stroke volume index (SVI), and systemic vascular resistance index (SVRI). After 60 minutes, subjects in both groups were re-assessed for clinical signs, USCOM, pulmonary edema using lung ultrasound score (LUS), and liver span. Subjects were blinded as to the protocol they received. We compared 24-hour and 72-hour mortality rates, clinical improvement of shock at 60 minutes, cardiac index (CI), stroke volume index (SVI), and systemic vascular resistance index (SVRI), as well as pulmonary edema and hepatomegaly, between the two groups. Results At 60 minutes after resuscitation, there were significant differences between the ACCM and USFR groups in the proportion of clinical improvement (0/18 vs. 5/18, P=0.016), pulmonary edema (15/18 vs. 4/18, P<0.001), and hepatomegaly (16/18 vs. 5/18, P<0.001). Mortality rates at 24 hours and 72 hours in the ACCM vs. USFR groups were 17% vs. 12% (P=0.199) and 78% vs. 39% (P=0.009), respectively. Conclusion The USFR protocol reduces the occurrence of fluid overload and leads to a lower mortality rate at 72 hours compared to the ACCM fluid resuscitation protocol.